Study of genus Neoperla (Plecoptera: Perlidae) from the Philippines - Sivec, Ignac (Scopolia, 1984)
The Philippines have a distinct fauna of shered or closely related species of Neoperla. Some species from the same locality and not only from different islands reveal great variability. Based on the study of types of all previously named taxa (several lectotypes desinated) the following species arerecognized, described, illustrated and identified in the key (adults only):N. recta BANKS (= N. incerta KLAPÁLEK; new synonymy; = N. viscayana BANKS, new synonymy); N. pseudorecta spec. nov.; N. zwicki spec. nov.; N.nishidai spec. nov.; N. hermosa BANKS; N. pallescens BANKS; N. obliqua BANKS; (= N. apoana BANKS, new synonymy); N. jewetti spec. nov.; N. pallicornis BANKS; N. atripennis BANKS; N. oculata BANKS; N. wagneri spec. nov.; N. nigra spec. nov.; N. philippina spec. nov.; N. spec. ZWICK; N. flintispec. nov.; N. dendata spec. nov.; N. agusani spec. nov. Unassociated females of 9 species are given provisional letter designations.
Keywords: Plecoptera; Žuželke; Filipini; zoologija; zoology; entomologija; Neoperla